Collaborative procurement for developing a sustainable campus - Nifa F.A.A.; Rahim S.A.; Rani W.N.M.W.M.; Ismail M.N. (American Institute of Physics Inc., 2024)
It is particularly challenging to achieve sustainability in campus universities, where a high volume of users and activities has made it more imperative to promote green buildings that reduce energy and water consumption while having a minimal carbon footprint. At present, the frameworks for sustainable campus have seldom focused on the project procurement method which would improve construction team integration in developing the physical aspect of campus development. Therefore, in response to that challenge, this paper investigates how the delivery team, responsible for the design and construction of a project, can be integrated to work together more efficiently and more using the collaborative procurement method known as partnering. This paper reports part of a previous research and sets the base for ongoing research on the critical factors in partnering for sustainable campus development. The outcome or result of this study will meet and support the requirement for construction, maintenance, and operation process for universities towards sustainable building/campus in the future. 2016 Author(s).